Excessive Alcohol Consumption and Risk Behaviors in Argentine Adolescents - TEMPORELLI, KARINA; Viego, Valentina (Horizonte Sanitario, 2024)
Objectives: Given the increase in alcohol consumption in the youth population and the potential physical and mental risks that this situation causes, this work analyzes the conditioning factors of excessive alcohol consumption in the population between 13 and 17 years of age in Argentina.Materials and Methods: We use data from the World Survey of School Health, applied to a representative sample of 56,981 adolescents throughout the country in 2018. We estimate logistic regressions to identify conditional variables that influence the abusive intake of alcohol. Those factors include personal, socioeconomic, psychological, and situational independent variables.Results: An increase in alcohol consumption among adolescents has been observed, with a higher incidence among females. Situational factors, such as the availability of alcohol and peer pressure, are key determinants. There is a strong association between excessive alcohol consumption and risky behaviors, as well as an increase in the harms experienced by adolescents.Conclusions: The need to implement specific regulatory and protective measures is emphasized. The importance of comprehensive prevention and education strategies is highlighted, focusing on situational and social factors. Interventions should involve family, school, and community to reduce risks and promote healthy behaviors. Keywords: Binge Drinking, Health Risk Behaviors, Adolescents, Argentina.